2019
DOI: 10.5137/1019-5149.jtn.25891-19.2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of lacosamide in experimental traumatic spinal cord injury in rats

Abstract: AIM: To evaluate the effects of lacosamide on traumatic spinal cord injury (SCI) in rats. MATERIAL and METHODS: A total of 28 male Wistar albino rats, each weighing 300-350 g, were included. They were randomly assigned to four groups. In Group 1, only a laminectomy was performed; in Group 2, SCI was performed after laminectomy; in Group 3, SCI was performed after laminectomy followed by lacosamide administration, and in Group 4, SCI was performed after laminectomy followed by physiological saline administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…In the current study, we had similar results to our previous study (lacosamide treatment after spinal cord injury) 8) . Histopathological results represented that there is lower damage in group III which was treated with lacosamide when compared with the others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, we had similar results to our previous study (lacosamide treatment after spinal cord injury) 8) . Histopathological results represented that there is lower damage in group III which was treated with lacosamide when compared with the others.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported that it exhibits antioxidant, anti-inflammatory and lipid peroxidation inhibiting effect which are the main scope of the treatment strategy for neural damage after PNI 1,13,22) . We have also reported in our previous study that lacosamide has neuroprotective effects after spinal cord injury 8) . So, when consider the anti-inflammatory, antioxidant, and inhibiting lipid peroxidation properties and protective effects of lacosamide on neural tissue after experimental spinal cord injury, we hypothesized that it may provide neuroprotective effects after traumatic PNI.…”
Section: Introductionsupporting
confidence: 68%
“…LCM has also been shown to reverse the brain lipid peroxidation and to increase the SOD activity in a strychnine-induced seizure model [33]. Besides, LCM attenuates both the MDA levels in serum and the glial activation in a model of traumatic spinal cord injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with a previous study which has demonstrated that LCM decreased the formation of free radicals 48 h after SE induced by Pilo, since the authors reported reduced MDA levels and increased GSH levels [ 59 ]. Moreover, recent studies have revealed the antioxidant properties of LCM in an experimental model of traumatic spinal cord injury and lipopolysaccharide-induced neuroinflammation through increasing the levels of total antioxidant status in different brain areas such as the hippocampus, cortex, and cerebellum [ 60 , 61 ]. Chronic oxidative stress is also associated with cognitive dysfunction, therefore, the decrease of the levels of free radicals caused by LCM could have long-term effects and be responsible for the seizure attenuation and better cognitive performance of the animals treated with it during epileptogenesis, thus producing a disease-modifying effect such as preventing the occurrence of anxiety and depressive-like symptoms.…”
Section: Discussionmentioning
confidence: 99%